Surface water flooding, groundwater contamination, and enteric disease in developed countries: A scoping review of connections and consequences. (May 2018) - Andrade, L.; O'Dwyer, J.; O'Neill, E.; Hynds, P.
Abstract: Significant volumes of research over the past four decades has sought to elucidate the social, infrastructural, economic, and human health effects of climate change induced surface flooding. To date, epidemiological and public health studies of flooding events have focused on mental health effects, vector-borne diseases, and infectious enteric disease due to floodwater contact (i.e. typically low consumption rates). The inherent nature of groundwater (i.e. out of sight, out of mind) and the widely held belief that aquifers represent a pristine source of drinking water due to natural attenuation may represent the "perfect storm" causing direct consumption of relatively large volumes of surface flood-contaminated groundwater. Accordingly, the current study sought to systematically identify and synthesize all available peer-reviewed literature pertaining to the nexus between surface flooding, groundwater contamination and human gastroenteric outcomes. Just 14 relevant studies were found to have been published during the period 1980–2017, thus highlighting the fact that this potentially significant source of climate-related exposure to environmental infection has remained understudied to date. Studies differed significantly in terms of type and data reporting procedures, making it difficult to discern clear trends and patterns. Approximately 945 confirmed cases of flood-related enteric disease were examined across studies; these concurred with almost 10, 000 suspected cases, equating to approximately 20 suspected cases per confirmed case. As such, no regional, national or global estimates are available for the human gastrointestinal health burden of flood-related groundwater contamination. In light of the demonstrable public health significance of the concurrent impacts of groundwater susceptibility and climate change exacerbation, strategies to increase awareness about potential sources of contamination and motivate precautionary behaviour (e.g. drinking water testing and treatment, supply interruptions) are necessary. Mainstreaming climate adaptation concerns into planning policies will also be necessary to reduce human exposure to waterborne sources of enteric infection. Graphical abstract: Image 1 Highlights: Review of the nexus between flooding, groundwater contamination and enteric infection. Low number of studies identified from 1980 to 2017 (n = 14). Mechanisms of flood-triggered groundwater contamination under-investigated. Need for interdisciplinary collaboration when studying public health impacts of flood events. Significant work required to inform timely, spatially-specific mitigation strategies.